Add-on stereo channel selector / Nur Azidawati Abd. Razak and Norshahrizan Ahmad - Abd. Razak, Nur Azidawati; Ahmad, Norshahrizan (2003)
The Add-On circuit presented here is useful for stereo systems. This circuit has provision for connecting stereo outputs from four different sources or channels as inputs and only one of them is selected or connected to the output at any one time. This system have two choice to use either automatically or manually. So, the user can choose one of them. This system is easy to user when they used in automatically system because the channel will detect by itself. So, the user do not have the trouble to detect the channel by manually. In manually, the user must skip the switch by themselves.